Lower Diffusion‐Induced Stress in Nano‐Crystallites of P2‐Na2/3Ni1/3Mn1/2Ti1/6O2 Novel Cathode for High Energy Na‐ion Batteries. Issue 12 (15th January 2023) - Sengupta, Abhinanda; Kumar, Ajit; Barik, Gayatree; Ahuja, Aakash; Ghosh, Jit; Lohani, Harshita; Kumari, Pratima; Bhandakkar, Tanmay K.; Mitra, Sagar
Abstract: P2‐type Na2/3 Ni1/3 Mn1/2 Ti1/6 O2 (NMTNO) cathode is a preeminent electrode material for Na‐ion batteries owing to its open prismatic framework, air‐moisture stability, inexpensiveness, appealing capacity, environmental benignity, and Co‐free composition. However, the poor cycling stability, sluggish Na‐ion kinetics induced in bulk‐sized cathode particles, cracking, and exfoliation in the crystallites remain a setback. To outmaneuver these, a designing strategy of a mechanically robust, hexagonal nano‐crystallites of P2‐type Na2/3 Ni1/3 Mn1/2 Ti1/6 O2 (NMTNOnano ) electrode via quick, energy‐efficient, and low‐cost microwave‐irradiated synthesis is proposed. For the first time, employing a unified experimental and theoretical approach with fracture mechanics analysis, the mechanism behind the enhanced performance, better structural stability, and lower diffusion‐induced stress of NMTNOnano compared to micro‐sized Na2/3 Ni1/3 Mn1/2 Ti1/6 O2 is unveiled and the electrochemical shock map is predicted. The NMTNOnano cathode provides 94.8% capacity retention after 100 cycles at 0.1 C with prolonged performance for 1000 cycles at 0.5 C. The practical viability of this cathode, tested in a full cell against a hard carbon anode delivered 85.48% capacity retention at 0.14 mA cm −2 after 200 cycles. This work bridges the gap in correlating the microstructural and electrochemical properties through experimental, theoretical (DFT), and fracture mechanics analysis, thereby tailoring efficient cathode with lower diffusion‐induced stress for high‐energy Na‐ion batteries. Abstract : In this work, a mechanically robust, nanostructured Ti 4+ doped P2‐type Na2/3 Ni1/3 Mn1/2 Ti1/6 O2 has been designed as a highly proficient cathode material for high‐energy Na‐ion batteries. The nano‐crystallites boost the structural integrity during cycling thereby, enhancing the rate capability and cycle life. The study aims to bridge the correlation between microstructural and electrochemical properties through experimental, theoretical, and fracture mechanics analysis.